Acaricidal efficacy of crude extracts and isolated flavonoids from Calpurnia aurea subsp. aurea against Rhipicephalus turanicus - Naidoo, Vinny (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2017.